The Effectiveness of Kahoot as a Mathematics Learning Media on Learning Outcomes During the Covid-19 Pandemic - Islah Nurul Fadillah; Wati Susilawati; Hamdan Sugilar; Rahayu Kariadinata (UIN Sunan Gunung Djati Bandung, 2022)
This study discusses the effectiveness of mathematics learning media on learning outcomes during the Covid-19 pandemic. The learning media during the Covid-19 pandemic discussed in this study was Kahoot. Kahoot is one of the online mathematics learning media that presents quizzes in the form of questions presented in the form of games. The problem in this research is whether Kahoot is effective as a medium for learning mathematics on learning outcomes during the Covid-19 pandemic. The research method used is qualitative with descriptive analysis techniques with literature study, where this study tries to describe existing phenomena, present or past. Based on various scientific references, most of them state that learning using Kahoot can be said to be effective. So that the use of Kahoot in the online learning process during the pandemic is effective to use. This study aims to determine the effectiveness of Kahoot as a medium for learning mathematics during the Covid-19 pandemic